2022
DOI: 10.1186/s12913-022-07691-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial care responses to terrorist attacks: a country case study of Norway, France and Belgium

Abstract: Background The international terrorism threat urges societies to invest in the planning and organization of psychosocial care. With the aim to contribute to cross-national learning, this study describes the content, target populations and providers of psychosocial care to civilians after terrorist attacks in Norway, France and Belgium. Methods We identified and reviewed pre- and post-attack policy documents, guidelines, reports and other relevant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…The utilization of PCP and MHS after terrorist attacks could be different in countries with other health systems and/or different psychosocial care responses to terrorist attacks [ 48 ]. For instance, studies based on self-reported healthcare utilization suggest that the utilization of GPs was less common in survivors of the 13 November attacks in Paris, France than in survivors of the Utøya attack [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of PCP and MHS after terrorist attacks could be different in countries with other health systems and/or different psychosocial care responses to terrorist attacks [ 48 ]. For instance, studies based on self-reported healthcare utilization suggest that the utilization of GPs was less common in survivors of the 13 November attacks in Paris, France than in survivors of the Utøya attack [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As has been demonstrated in previous research, the organization of care and support after a terrorist attack varies widely between countries (e.g., Stene et al, 2022), not only with regard to the parties involved, but also in the degree to which an outreach approach is used whereby survivors are actively approached to refer to care. International guidelines recommend the monitoring of needs and problems of the survivors of disasters (Inter-Agency Standing Committee (IASC), 2007; Bisson et al, 2010;Te Brake and Dückers, 2013;Juen, 2016; International Committee of the Red Cross (IFRC), 2018; Dückers et al, 2022).…”
Section: Care and Supportmentioning
confidence: 93%
“…Disasters and humanitarian crises can have a tremendous impact on the mental health and psychosocial well-being of affected populations [1][2][3][4][5][6][7][8]. To adequately respond to mental health risks and problems, governments and partners at different levels, including governmental and non-governmental organizations and citizens, need to engage and collaborate on behalf of the planning and implementation of mental health and psychosocial support (MHPSS) in different stages of the disaster life cycle [9][10][11][12][13][14][15][16][17]. MHPSS has been defined as "any type of local or outside support that aims to protect or promote psychosocial well-being and/or prevent or treat mental disorder" [18] (p. 1).…”
Section: Introductionmentioning
confidence: 99%